Associated between hypertension and body mass index, cholesterol, and blood sugar levels in elderly women - Sufyan Anwar; Teuku Alamsyah; Safrida Safrida; Maiza Duana; Khairunnas Khairunnas; Enda Silvia Putri; Marniati Marniati; Teuku Muliadi (AcTion: Aceh Nutrition Journal, 2024)
Hypertension is a major public health problem in Indonesia, with the highest number of elderly female patients. This study aimed to assess the relationship between BMI, cholesterol, and blood sugar levels, and systolic and diastolic blood pressure in elderly women. An observational study was conducted using a cross-sectional design, in which 330 women in West Aceh District aged 60 years or older were included. Data were analyzed using simple linear regression and multiple linear regression tests to determine the relationship between independent variables (systolic and diastolic blood pressure) and dependent variables (BMI, cholesterol, and blood sugar levels). The results showed that the correlation between BMI, cholesterol, and blood sugar levels and systolic blood pressure was weak (r ≤ 0.25). The BMI with diastolic blood pressure was moderate (r=0.272). Conversely, the correlation between cholesterol and blood sugar levels and diastolic blood pressure was weak (r ≤ 0.25).  Multivariate analysis showed that BMI (p<0.001), cholesterol (p<0.001), and blood sugar levels (p ≤ 0.013) were significantly associated with systolic blood pressure. Furthermore, diastolic blood pressure was significantly associated with BMI (p <0.001). In conclusion, BMI is associated with systolic and diastolic blood pressure, while cholesterol and blood sugar levels only contribute to systolic blood pressure but not diastolic blood pressure.